Bowling alone or distancing together? The role of social capital in excess death rates from COVID19. (September 2021) - Fraser, Timothy; Aldrich, Daniel P.; Page-Tan, Courtney
Abstract: Much attention on the spread and impact of the ongoing pandemic has focused on institutional factors such as government capacity along with population-level characteristics such as race, income, and age. This paper draws on a growing body of evidence that bonding, bridging, and linking social capital - the horizontal and vertical ties that bind societies together - impact public health to explain why some U.S. counties have seen higher (or lower) excess deaths during the COVID19 pandemic than others. Drawing on county-level reports from the Centers for Disease Control and Prevention (CDC) since February 2020, we calculated the number of excess deaths per county compared to 2018. Starting with a panel dataset of county observations over time, we used coarsened exact matching to create smaller but more similar sets of communities that differ primarily in social capital. Controlling for several factors, including politics and governance, health care quality, and demographic characteristics, we find that bonding and linking social capital reduce the toll of COVID-19 on communities. Public health officials and community organizations should prioritize building and maintaining strong social ties and trust in government to help combat the pandemic. Highlights: This study examines excess death rates during the COVID19 pandemic among US counties. We use a panel dataset of counties over 6 time-steps from February to September 2020. We identified more comparable samples using coarsened exact matching, different only by social capital. Bonding and linking social capital were associated with fewer excess deaths in US counties. Bonding social capital was effective in spring, and linking social capital in summer.